Os efeitos fisiológicos de um protocolo de exercícios dentro e fora da água em idosas que usam ou não fármacos cardiovasculares - Rosa, Ignaldo Paz da (2013)
Physical activity has great influence in health, taking part on a successful aging through physiological mechanisms, some of them not well known. Objective: Evaluate the effects of heart rate and blood lactate from a protocol of exercises in and outside the water on physically active elder, that practice hydrogymnastics and adminisrated or not cardiovascular medicines. Methods: longitudinal, observational, analytic and prospective study on elderly women who are sixty years old or more with 6 months practice of hydrogymnastic on the swimming school from Parque Esportivo da Pontificia Universidade Catolica do Rio Grande do Sul (PUCRS), Brazil and that administrated cardiovascular medicine,other medicines or none. It was applied a roll of exercises in two rounds. One of them inside the water and other outside, each of them contained the practice of 18 exercises set on 3 rounds of 6 exercises, in which each round had three exercises of small amplitude (running, side-running, back-running) and three exercises of high amplitude (front Kick, side kick and anthero posterior kick). They were set on a music rhythm of 120 bpm, during 10 minutes and 30 seconds (no interruption). For the analysis, the Exato de Fischer test, test t student, Wilcoxon and Mann- Whitney. The level of significance was of 5%. Results: There participated 14 elder women average age from 67,29±4,61 years old (8 of them under the administration of cardiovascular medicines an average age of 68,73 ± 4 years old, 3 of them under administration of other medicines and average age of 66,33 ± 46,62 years old and 3 with no use of medicines and average age of 64,67± 1,97 years old ). There was a reduction of blood lactate on the cardiovascular group inside and outside the water of 3,92±1,27 to 2,42±0,92, respectively (p=0,023). there was no difference in HR inside and outside water from different medicine groups. Conclusion: The comparison between heart rate and lactate among elder women wether using or not medicines from cardiovascular field has shown no significative difference, even in or outside the water. The elder women that practiced exercises outside the water showed a rise on the blood lactate level significantly higher in relation to those who practiced exercises inside the water, even in the group that uses or doesn't use cardiovascular medicines.